RADIATION CREATION AND ANNEALING NANO SIZE DEFECTS IN NaCl CRYSTALS - Baimakhanuly, A. (Recent Contributions to Physics, 2008)
Creation of radiation defects was investigated in NaCl crystals irradiated at 300 K by heavy Au ions, a particles, X-rays as well as XeCl or ArF laser radiation selectively forming in two-photon regime anion excitons or hot electron-hole pairs. The emission of self-trapped excitons and tunnel recombination of electrons (staring from two states of an F centre) with spatially close self-trapped holes were separated in cathodoluminescence and phosphorescence spectra at 6 K. The hopping diffusion of I and H interstitials is accompanied by thermally stimulated luminescence at 15-27 and 30-45 K, respectively.